THE RELATIONSHIP OF DIGITAL LITERACY ABILITY WITH STUDENTS' COGNITIVE LEARNING OUTCOMES - Fathia Zaitun Azzahro; Bunga Ihda Norra; Chusnul Adib Achmad (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2023)
The development of technology and information in the 21st century affects all components of life, which makes people make sudden transitions. Digital literacy is urgently needed in the world of education to equip students' abilities and skills in 21st century learning. The ability needed is a person's ability to use digital technology and information appropriately and responsibly. However, the rapid development of technology has a negative impact on its users. This study aims to determine whether there is a relationship between digital literacy skills and students' cognitive learning outcomes. This type of research is correlational quantitative. The population of this study was class XI MAN Temanggung with a total of 182 students. The sampling technique with simple random sampling was 72 students of class XI MIPA. Data collection techniques with questionnaires, tests, interviews and documentation. The results showed that there was no significant relationship between digital literacy skills and the cognitive learning outcomes of Temanggung MAN students in excretion system material with a significant value of 0.307 > 0.05.